The Relationship between Giftedness and Sex and Children's Theory of Mind Skills and Social Behavior - Abdullah Bozkurt; Zekai Ayık (MDPI AG, 2024)
Background: Theory of mind (ToM), the ability to recognize the mental states and emotions of others, is central to effective social relationships. Measuring higher-order ToM skills in gifted children may be a useful way to identify the tendency to experience difficulties in social behavior. The aim of this study was to investigate the relationship between intelligence and sex in children using ToM and social behavior measures. Methods: Children aged 10-12 years constituted both the gifted (n = 45) and non-gifted (n = 45) groups. The participants were assessed for prosocial behaviors and peer problems using the subscales of the Strength and Difficulties Questionnaire and in terms of ToM using the Reading the Mind in the Eyes Test-Child Version (RMET-C) and the Faux Pas Recognition Test-Child Version (FPRT-C). Results: ToM test results were higher in gifted children and girls. Peer problems were lower in gifted children. Prosocial behavior was higher in girls. No relationship was determined between ToM tests and peer problems or prosocial behavior in gifted children, but such a relationship was observed in the non-gifted group. Conclusions: This study shows that gifted children with high cognitive skills also possess superior social cognition skills. Advanced ToM skills in gifted children may be important to supporting their social and cognitive development. The differences between boys and girls should be considered in educational interventions applied to children in the social sphere.